Analysis of motivational strategies used by principals to solve the challenges in management of support staff in public secondary schools, Nyamira County, Kenya. - Nyaboga, Nyagaka Evans; Ajowi, Jack; Bosire, Joseph N. (fssh-journal.org, 2018)
The study was necessitated by the need to analyze motivational strategies used by principals to solve the challenges in management of support staff in public secondary schools in Nyamira County, Kenya. The following summary of the findings, conclusions and recommendations were made: (1) The study established that principals and support staff employs a number of strategies that enable them to cope with the challenges they face, such motivational strategies are as follows. (2) Support staffs were encouraged to own the schools and were asked to assist the school by carrying tools from home. (3) Staff members were being motivated to wake up very early to go work by being offered all the meals in school starting with break-fast. (4) Support staffs stayed in their villages and helping their schools in addressing the problem of housing. (5) Support staffs were being requested to double up duties because staff shortage in the schools. (6) The main coping strategy that were motivating the support staff were: engaging in small scale businesses; carrying tools from home, renting houses at nearby market centers and taking loans. The principals were partly offering financial assistance to the support staff.
Keywords: Public secondary school; staff motivation; Support staff